Fictional environments : mimesis, deforestation, and development in Latin America - Saramago, Victoria, 1985- (FlashPoints (Evanston, Ill.) ;, 2021)
"Fictional Environments: Mimesis, Deforestation, and Development in Latin America investigates how fictional works have become sites for the production of knowledge, imagination, and intervention in Latin American environments"--